Environmental effects of the 1978 Sunnyside Mine flood - Arnold, Victoria S., author; Ridley, John, advisor; Wohl, Ellen, committee member; Bareither, Chris, committee member (Colorado State University. Libraries, 2024)
In 1978, the pillar of rock and sediment between Lake Emma and the Sunnyside Mine collapsed, draining 5-25 M gallons (19-95 ML) of water and sediment through the mine and the American Tunnel within a few hours (Thompson, 2018). This caused a major flood in Cement Creek, a tributary of the Animas River north of Silverton, Colorado. Although work has been done on the geochemistry of mine outwash in the same drainage from the 2015 Gold King Mine spill, the material from the Sunnyside Mine flood has not been extensively studied previously. This study aims to determine whether the 1978 Sunnyside Mine flood had significant geochemical and geomorphic effects and continues to affect the environment today. Likely flood deposits were identified approximately fifteen centimeters above the typical spring flood level based on sediment characteristics, interviews with witnesses to the flood and community stakeholders, as well as newspaper articles and photographs from shortly after the flood. Cement Creek sediment samples from flood and non-flood deposits were analyzed with VNIR spectroscopy for mineralogy. Sediment samples from the Sunnyside flood contained vermiculite, iron smectite, zeolites, gypsum, and secondary copper minerals, while most stream sediment included ferrihydrite, K-illite, and vermiculite. Sediment samples were also analyzed for their bulk elemental geochemistry, which revealed that the Sunnyside flood sediments had lower concentrations of heavy metals than the other sediments in Cement Creek, but had 59% more iron and 518% more sulfur. It is not clear whether the increased iron and sulfur exist as unweathered sulfides or as sulfates, but if there are sulfides or secondary sulfate minerals present in the flood sediment, then the flood sediment has significantly more acid generation potential than the other sediment in Cement Creek. Additionally, the average Fe/Cu ratios of the flood sediment is higher than the non-flood sediment, which indicates that the material is either from a different source, or that the flood water had lower pH than the water in Cement Creek when the other sediments were deposited. The significant difference in the minerals present and the elemental geochemistry, as well the continued preservation of flood horizon sediments, indicate that the Sunnyside Mine flood impacted the Cement Creek watershed. Understanding the impact that a major disaster like the Sunnyside Mine flood had on the area is important to have a better picture of a region that continues to face environmental impacts from mining activities.
Zip file contains CSVs for Appendix D1 and Appendix E.
Keywords: Animas River; mining; water quality; Cement Creek; acid mine drainage; sediment chemistry